Preventing hepatitis B virus infection among healthcare professionals: potential impact of a 2-dose versus 3-dose vaccine - Catherine Stevenson; Ji-Hee Youn; Mary S Hayney; Coline David (Taylor & Francis Group, 2021)
The exposure risk to the highly infectious hepatitis B virus (HBV) is an established and recognizable hazard to healthcare professionals (HCPs). In the United States, implementing preemptive vaccination programs and safety procedures resulted in drastic reductions in HBV infections among HCPs; however, many HCPs remain unprotected and risk of exposure persists, especially among those first entering a healthcare system and undergoing professional training. First-generation HBV vaccines require completion of a 3-dose schedule over a 6-month interval for maximum immunogenicity. By comparison, HepB-CpG (HEPLISAV-B®) is a 2-dose HBV vaccine licensed in the United States in 2017, inducing rapid seroprotection over a 1-month interval and may represent a more effective strategy for combating HBV infection in US healthcare systems. In this modeling study, the health and economic impact of implementing an HBV vaccination strategy with HepB-CpG versus the 3-dose HBV vaccine (Engerix-B®) was evaluated among HCPs newly entering a healthcare system. The model used effective seroprotection rate, a real-world metric accounting for HCP vaccine compliance and seroprotection rates for different dosing regimens and considered current pricing for postexposure prophylaxis treatment. Compared with the 3-dose vaccine, HepB-CpG was anticipated to provide faster, increased protection against HBV infection among newly entered HCPs. In protecting a greater percentage of HCPs, HepB-CpG was also projected to substantially reduce the risk of HBV exposure. Accordingly, an economic analysis showed HepB-CpG vaccination would reduce costs of postexposure prophylaxis treatment compared with the 3-dose vaccine. Overall, HepB-CpG represents an effective therapeutic strategy against HBV infection for US healthcare systems.